AI, LA, ALI e AQUI: gramaticalização de um paradigma emergente no domínio funcional da especificação nominal - Confessor, Francisco Wildson (2013)
In the light of the Functional Linguistic Theory, in its North-American version (HOPPER, 1987, 1991, 1998, 2008, 2010; GIVÓN, 2001; LEHMANN, 2002; HOPPER; TRAUGOTT, 2003; FURTADO DA CUNHA; OLIVEIRA; MARTELOTTA, 2003, among others), the general objective of this research is to demonstrate, based on morphosyntactic and semantic-pragmatic properties, that AQUI (HERE), AÍ, ALI and LÁ (THERE) are part of an emerging paradigm in Brazilian Portuguese recently constituted and still developing of forms indicating specificity in indefinite noun phrases (NP). The data that make up the corpus of this research were collected in the following large Brazilian oral corpora: the Corpus Discurso & Gramática: a língua falada e escrita na cidade de Natal (FURTADO DA CUNHA, 1998), the Banco Conversacional de Natal (FURTADO DA CUNHA, 2010), the Projeto Variação Linguística no Estado da Paraíba VALPB (HORA, 2005) and the Projeto Variação Linguística Urbana na Região Sul do Brasil VARSUL (VANDRESEN, 2002). Firstly, the behavior of the specificity markings AQUI, AÍ, ALI and LÁ is described with respect to many factors of morphosyntactic and semantic-pragmatic nature: type of construction in which the markers appeared; existence or not of intervening material between the specificity marker item and the NP s nuclear noun; type of noun to which AQUI, AÍ, ALI and LÁ are linked; syntactic function of the specified SN; informational status of the NP to which the specificity markers AQUI, AÍ, ALI and LÁ are attached; occurrence of conversational implicatures (GRICE, 1982) in the context of use of these specificity markers. Next, a possible grammaticalization trajectory is outlined, according to which AQUI, AÍ, ALI and LÁ would had gone from an early spatial deictic indication to the specificity indication. The results point to the existence of forms with varying degree of emergence in this new paradigm of nominal specification, with AÍ being, probably, the item most grammaticalized, followed by LÁ, then ALI and AQUI, which permanence in the paradigm do not yet appear to be consolidated